Association between Monocyte to High-Density Lipoprotein Cholesterol Ratio and Nonalcoholic Fatty Liver Disease: A Cross-Sectional Study. (7th December 2021) - Huang, Hangkai; Wang, Qinqiu; Shi, Xiaoying; Chen, Yishu; Shen, Chao; Zhang, Juanwen; Xu, Chengfu
Abstract : Background . The aim of the present study was to investigate the association between monocyte to high-density lipoprotein cholesterol ratio (MHR) and nonalcoholic fatty liver disease (NAFLD) in Chinese population. Methods . We enrolled 14189 individuals who attended their annual health examinations in the study. We performed the anthropometric and laboratory measurements and diagnosed NAFLD by hepatic ultrasonography without evidence of other etiologies of chronic liver disease. Student's t -test, Mann–Whitney U test, and chi-squared ( χ 2 ) test was used to compare the differences of clinical characteristics between participants with or without NAFLD. Pearson's and Spearman's analyses were performed to assess the correlation of MHR and NAFLD risk factors. Univariate and multivariate logistic regression analyses were conducted to explore whether MHR associated with NAFLD. Results . Thirty-five percent of the participants enrolled were diagnosed with NAFLD. Compared with healthy controls, NAFLD patients were male predominant, older, and had higher body mass index, waist circumference, and systolic and diastolic blood pressure, as well as higher levels of alanine aminotransferase, aspartate aminotransferase, γ -glutamyl transferase, triglyceride, total cholesterol, low-density lipoprotein cholesterol, fasting plasma glucose, glycated hemoglobin A1c, and serum uric acid, but lower levels of serum high-density lipoprotein cholesterol. Besides, MHR was significantly higher in NAFLD patients than healthy controls [5.35 (4.18–6.84) versus 4.53 (3.48–5.93), P < 0.001 ]. MHR quartiles were positively related to the prevalence of NAFLD (P < 0.001 for trend). In multivariate logistic regression analysis, MHR was positively associated with the risk of NAFLD after adjusting age, gender, body mass index, waist circumference, diastolic blood pressure, alanine aminotransferase, triglyceride, total cholesterol, fasting plasma glucose, and serum uric acid (OR: 1.026, 95% CI: 1.002–1.052; P = 0.037 ). Conclusions . MHR is significantly and positively associated with the risk of NAFLD.